Diversidad, patrones de distribución y “hotspots” de los equinoideos irregulares (Echinoidea: Irregularia) de México - Caballero-Ochoa, Andrea Alejandra (2017)
Diversity, distribution patterns and hotspots of the irregular equinoids (Echinoidea: Irregularia) of Mexico.Irregular echinoids can be found in almost all marine habitats, from the polar to the equatorial regions, and from the intertidal zone to great depths; some species have a cosmopolitan distribution, but most are geographically restricted, and all live in very particular habitats to a greater or lesser degree in Mexico has 153 species distributed within the coastal limits. Geographic barriers (terrestrial barriers and large ocean basins) and ocean current patterns act as primary modulators of the distribution of echinoids; however, there are factors that define the local distribution. The purpose of this work is to analyze the diversity of irregular echinoids in Mexico, as well as to explain the patterns of distribution and to explore the hotspots through panbiogeography as units of high richness. The study area covers all the territorial waters of Mexico in the Pacific Ocean, Atlantic and Caribbean Sea. To obtain the geographical coordinates we used the distribution data of 68 species of irregular echinoids recorded at different depths. We reviewed the specimens deposited in five scientific collections, in addition to the revision of other records from online databases: 1. National Collection of Echinoderms “Ma. Elena Caso Muñoz” of the Instituto de Ciencias del Mar y Limnología (ICML), of the Universidad Nacional Autónoma de México (UNAM); 2. Regional Collection of Invertebrates of the Academic Unit Mazatlán, ICML, UNAM. 3. Invertebrate Zoology Collection, Smithsonian Museum of Natural History, Washington, D.C., United States of America, (USA); 4. Invertebrate Collection, Museum of Comparative Zoology, University of Harvard, Boston, Massachusetts; 5. Invertebrate Zoology, Peabody Museum, Yale University, New Haven, Connecticut; National Information System on Biodiversity (SNIB-CONABIO) and Global Biodiversity Information (GBIF). The generalized tracks were performed by the analysis of endemicity based on the optimization method, using the NDM/VNDM program with a 2° x 2° latitude/longitude grid. Hotspots were obtained by overlapping the generalized tracks using the ArcView program. The best represented was family Brissidae, with 15 species, most of them belonging to the genus Brissopsis, followed by the family Mellitidae (with 12 species), half of them belongs to the genus Encope. The families of irregular sea urchins with a smaller number of species were: Echinoneidae, Plexechinidae, Palaeotropidae and Paleopneustidae, each represented by a single species. The following general patterns of distribution were recognized: 1) groups of widely distributed species and 2) restricted species living in the first few meters of depth (0-20m). Nine consensus areas or generalized tracks were obtained in the Endemicity Analysis and 47 hotspots were recognized. Three areas with high specific wealth were obtained: West Coast of the Gulf of Mexico, Bank of Campeche/Mexican Caribbean and Gulf of California. The Gulf of California area has the highest diversity of irregular echinoids. This is the first approximation in the study of the panbiogeography of echinoderms of Mexico. Rev. Biol. Trop. 65(Suppl. 1): S42-S59. Epub 2017 November 01.